POTENSI TURUBUK (Saccharum Edule Hassk) UNTUK MENINGKATKAN SISTEM IMUN DITINJAU DARI KANDUNGAN GIZI DAN AKTIVITAS ANTIOKSIDAN - Erina Febiani (2021)
The study was conducted to determine the nutritional value and antioxidant activity contained in turubuk (Saccharum Edule Hassk) a typical plant in Loji, Karawang, which has the potential to increase the body's immune system. Turubuk samples were selected based on three different locations, namely Gunung Sangga Buana, Gunung Celincing and Puncak Sempur. Analysis of nutritional value using the proximate method which consists of air content, ash content, protein content, fat content and carbohydrate content. The results obtained were: 89.19% moisture content, 1.43% ash content, 4.59% protein content, 0.86% fat content and 3.55% carbohydrate content. Analysis of antioxidant activity using the DPPH method obtained results of 3.88% w / v. Analysis of Vitamin C and Vitamin B6 obtained results of vitamin C <0.07 mg / kg, vitamin B6 0.54 mg / kg. Then for phenol analysis the results were 20.13 mg / kg.